A System for Movement Detecting Congestion. - R, Reeja S.; Kavya, Dr. N. P. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
In this paper, we present a system for tracking and provide early information of hazardous locationsin huge gatherings. It is based on optic flow estimations and detects sequences of crowd motion that are characteristic for devastating congestions. For optic flow computation, Lucas- Kanade method is employed to determine the optical flow vectors for the gathered video. Segmentation of video sequences is done and optic flow is determined for respective segments. A threshold optic flow is chosen in such a way that the tracking of congested area in video is easilydoneby comparing it with respective segmentâ€™s determined optic flow values. Finally, we present the location of crowd congestion which helps in taking further protective measures to handle unusual events.Â Â